Монгол ардын хөгжим өгүүлэх эрхтэнтэй шүтэлцэх төрөл зүйлсийн ангиллын асуудалд : On the classification of Mongolian folk music and its coherence to speech organs - Л., Хэрлэн (Mongolian Studies, 2023)
Mongolian folk art is correlated with speech organs or articulators including khoomii, tsuur, isgeree, aman huur or harmonica and amaar tashih deldeh. The characteristics of each of them are defined depending on in which part of the speech organs sound is created as the air travels from lungs. For example, if the sound is created in the larynx, khoomii organ and oral cavity, it is called khoomii; if in oral cavity and labial area, then it is isgeree and if the sound is created in musical instrument with the participation of airstream and speech organs, it is called aman khuur or harmonica.